Model study of the salt accumulation effect on the membrane performance in osmotic membrane bioreactor - Xiao, Dezhong. (2011)
Recently, a novel osmotic membrane bioreactor (OsMBR) was developed which utilized a forward osmosis (FO) membrane module to replace the microfiltration/ultrafiltration in the conventional MBR system. Such system exhibited very high rejection of various contaminants and mineral salts due to the nature of FO membrane. On the other hand, this high rejection also caused the accumulation of salts in the reactor which could have adverse impact on the biological activities as well as the membrane filtration performance. In this project, a FO model was developed based on internal concentration polarization (ICP) theory, and the experimental results from independent FO tests for both initial flux and continuous flux performance matched the model predictions very well, which verified the model developed and proved the dominant role of ICP in FO’s flux performance. Hence, the mass balance equation of an OsMBR system was coupled with the ICP model to simulation the effects of salt accumulation on the system performance in membrane filtration aspect. Systems operated under two possible sludge wastage strategies – impulse wasting and continuous wasting were simulated and the results were presented and analyzed. Under impulse sludge wasting condition, water flux kept decreasing before the wastage was carried out. The flux performance would be affected by different draw solution concentration, membrane orientation, reactor size and inflow water salt concentration. To maintain a minimum flux level, the impulse wasting needed to be carried out at a system dependent frequency. Oppositely, a stable flux occurred after a period of filtration under continuous sludge wasting condition, and the salt concentration in the reactor also reached maximum at the same time. The level of the stable flux was controlled by the sludge wastage flow rate and the time scale to reach the stable flux could be indicated by the solids retention time (SRT) of the system. Membrane orientation was also found to affect the degree of flux reduction and the stable flux.